2010
DOI: 10.1007/s00405-010-1438-1
|View full text |Cite
|
Sign up to set email alerts
|

How smell tests experience and education affect ENT specialists’ attitudes towards smell disorders? A survey study

Abstract: The aim of the present study was to assess the effect of smell tests experience and education during residency or in general practice on ENT specialists' attitudes toward smell disorders in concern of their management strategies. Methodology included a voluntary and anonymous self-administered questionnaire survey conducted in Turkey and responses from 218 questionnaires were pooled and evaluated. Results stated that only 7.3% of the respondents reported currently using smell tests in their practice, and most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Nevertheless, few otolaryngologists have enough knowledge on olfaction disorders. 8 A recent study in Turkey indicated that 83.5% of otolaryngologists did not observe the implementation of standardized olfaction assessment tests during the residency period. 8 The lack of knowledge and training of physicians in their daily practice can lead to misdiagnosis and mismanagement of olfaction disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, few otolaryngologists have enough knowledge on olfaction disorders. 8 A recent study in Turkey indicated that 83.5% of otolaryngologists did not observe the implementation of standardized olfaction assessment tests during the residency period. 8 The lack of knowledge and training of physicians in their daily practice can lead to misdiagnosis and mismanagement of olfaction disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, physicians with greater knowledge about these disorders tend to consider the disease to be more important, and therefore achieve better diagnosis and treatment. 8 …”
Section: Introductionmentioning
confidence: 99%
“…Cultural discrepancies and the subjective nature of smell function make it difficult to validate a smell test for worldwide application [10]. This may explain the low interest of physicians in the smell function of patients with nasal polyps [11]. Smell function protects from dangerous substances like spoiled food and plays an important role in taste function, emotional status and quality of life [12].…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory dysfunction can also be an early biomarker of neurodegenerative diseases, including Alzheimer’s disease and Parkinson’s disease, where olfactory deficits precede detectable memory loss (6). Despite the impact of olfactory disorders on patients and their known associations with other serious health conditions, olfactory function is infrequently tested in routine clinical practice (7).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the impact of olfactory disorders on patients and their known associations with other serious health conditions, olfactory function is infrequently tested in routine clinical practice (7).…”
Section: Introductionmentioning
confidence: 99%